Superconducting Properties of Bi2-xPb0.3WxSr2Ca2Cu3O10+ï¤ Compounds - Tuama, Mohammed J.; Abbas, Lamia K. (Iraqi Journal of Science, 2021)
The conventional solid-state reaction method was utilized to prepare a series of superconducting samples of the nominal composition Bi2-xPb0.3WxSr2Ca2Cu3O10+d with 0â‰¤xâ‰¤0.5 of 50 nm particle size of tungsten sintered at 8500C for 140h in air . The influence of substitution with W NPs at bismuth (Bi) sites was characterized by the X-ray diffraction (XRD), scanning electron microscopy (SEM) and dc electrical resistivity. Room temperature X-ray diffraction analysis revealed that there exists two phases, i.e. Bi-(2223) and Bi-(2212), in addition to the impurity phases of (SrCa) 2Cu2O3, Sr2Ca2Cu7OÎ´, Ca2PbO4, CaO, and WO. It was found that the crystallographic structure of all samples was orthorhombic. Lattice parameter values and the volume fraction of the (2223)-phase of the prepared samples were also calculated. The superconductivity transition temperature (Tc) for samples subjected to substitution with W NPs was found to be higher than that for the pure sample. The optimal value of W NPs content in (Bi, Pb)-2223 system was found to be at x=0.3.